From share issue privatisation to non‐tradable share reform: a review of privatisation in China. (November 2016) - Xie, Feng; Chi, Jing; Liao, Jing
Abstract: Privatisation in China has proceeded on a gradual path over 30 years. In this paper, we present a detailed review of China's privatisation programmes from its Share Issue Privatisation (SIP) to its Non‐tradable Share (NTS) reform. The SIP was a primary offering process with state‐owned enterprises (SOEs) issuing new shares to private investors, but after their Initial Public Offering (IPO) approximately two‐thirds of the shares remained non‐tradable and were mainly held by the government. The SIP achieved only limited success because of its partial trading and partial privatisation, which led to the implementation of the NTS reform in 2005. The NTS reform aimed to dismantle the split share structure and provide opportunities for improving corporate governance and further privatisation. The review shows that the NTS reform has yielded greater success in improving firm performance and corporate governance than the SIP.